2014
DOI: 10.1007/s10750-014-2037-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of carbaryl resistance in the water flea Daphnia: complex interactions between inbreeding, stress, and selection

Abstract: Human impact often leads to reduced population sizes, and populations exposed to anthropogenic stress may suffer reduced evolutionary potential because of loss of adaptive genetic variation and higher risk of inbreeding depression (ID). Here, we exposed naive and carbaryl-selected inbred and outbred subpopulations of Daphnia magna to the pesticide carbaryl shortly after birth, and monitored acute (day 1-4) and post-exposure mortality (day 5-second clutch). Overall, acute mortality was lower than post-exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Furthermore, energy investment in detoxification mechanisms can imply a reduction of energy fluxes to important life-history traits, such as reproduction [86,87] and development time [88]. Moreover, clonal sorting and population size reductions during strong selection may erode the genetic diversity of the population and reduce effective population sizes, causing a risk for inbreeding [89], which can hinder the population's capability to adapt to other stressors. Cambronero et al [90] showed that negative impacts of historical exposure to carbamate increased when combined with a rise of temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, energy investment in detoxification mechanisms can imply a reduction of energy fluxes to important life-history traits, such as reproduction [86,87] and development time [88]. Moreover, clonal sorting and population size reductions during strong selection may erode the genetic diversity of the population and reduce effective population sizes, causing a risk for inbreeding [89], which can hinder the population's capability to adapt to other stressors. Cambronero et al [90] showed that negative impacts of historical exposure to carbamate increased when combined with a rise of temperature.…”
Section: Discussionmentioning
confidence: 99%